2017
DOI: 10.1111/pace.13180
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of aging based on the analysis of heart rate variability

Abstract: The use of neural network computations and the modification of the algorithm through the construction of individual training samples for different age intervals, and the creation of individual ensembles of classification neural networks, therefore achieved a prediction of the age of examined persons based on the values of their time and frequency domain heart rate variability indices, with 87% accuracy for women and 85% accuracy for men in the 66-85 years age interval and at least 85% for age groups across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
2
0
3
Order By: Relevance
“…The aging process is related to a reduction in the interaction ability of biological systems including the ANS (Lakatta and Levy, 2003;Niccoli and Partridge, 2012;Chadda et al, 2018). Multiple studies have shown that HRV decreases with age (Corino et al, 2006;Almeida-Santos et al, 2016;Botsva et al, 2017). However, it should not be ignored that some of the HRV indices show a non-linear decreasing pattern as age increased.…”
Section: Discussionmentioning
confidence: 99%
“…The aging process is related to a reduction in the interaction ability of biological systems including the ANS (Lakatta and Levy, 2003;Niccoli and Partridge, 2012;Chadda et al, 2018). Multiple studies have shown that HRV decreases with age (Corino et al, 2006;Almeida-Santos et al, 2016;Botsva et al, 2017). However, it should not be ignored that some of the HRV indices show a non-linear decreasing pattern as age increased.…”
Section: Discussionmentioning
confidence: 99%
“…Регуляцію АНС досліджували методом аналізу варіабельності ритму серця (ВРС) за допомогою монітора фірми «ЮТАС» (Україна) відповідно до міжнародних стандартів [11]. Для аналізу хвильової структури серцевого ритму використовували метод розрахунку спектра потужності, що базується на швидкому перетворенні Фур'є.…”
Section: матерIали та методиunclassified
“…Проводили кореляційний аналіз за Пірсоном. Критичним рівнем статистичної значущості приймали 0,05. з ризиком виникнення серцево-судинних та цереброваскулярних захворювань [11]. Тому виявлений дисбаланс АНС з відносним переважанням симпатичних впливів у людей похилого віку із ПТГ має несприятливе прогностичне значення.…”
Section: матерIали та методиunclassified
See 1 more Smart Citation
“…Generally, a higher HRV has been generally associated to a) better health, b) good balance between sympathetic and parasympathetic (vagal) system, c) better aging, and d) better cardiovascular and metabolic state. [46][47][48][49][50][51] Regarding the ANS interaction with the inflammatory cascade, a number of publications have ascertained the antiinflammatory role of the cholinergic parasympathetic system. 42,[52][53][54] Conversely, a chronic hyperactivity of the sympathetic ANS branch has been linked to a series of negative, proinflammatory, and other deregulated (immuneendocrine mainly) biochemical pathways.…”
Section: Introductionmentioning
confidence: 99%